Modeling and vibration control of a gantry crane - Zainal, Zairulazha (2005)
The aim of this project is to model industrial gantry cranes for investigations of dynamic behavior of the system. A gantry crane incorporating a payload is considered. The modeling technique which is easier in terms of mathematical derivation is chosen. Comparison between the mathematical model derived and previous work is conducted to validate the dynamic model. A simulated time response and vibration frequency of the system to an input command is presented. Furthermore, a vibration control scheme based on an open-loop filtering technique is developed. Finally, the effectiveness of the controller is investigated in terms of time response, level of vibration reduction, robustness and the capability of handling a payload.